Pendidikan Kesehatan Mengenai Tanda Bahaya Kehamilan Pada Ibu Hamil Di Puskesmas Gedong Air Bandar Lampung - Rilyani Rilyani; Muhammad Fiqi Dwiartho; Riswan Hadi; Najamuddin Dalimunthe; Ika Saraswati; Mutiara Natalia; Neisa Adhani; Endah Fajrianti; Putri Indaman; Siti Herlina Mariyam; Mia Nurar Lina (Compromise Journal Community Proffesional Service Journal, 2024)
Symptoms that indicate the need for attention for the mother and fetus are known as danger signs of pregnancy. To better recognize early signs of pregnancy risks, expectant mothers should schedule regular check-ups, which can help identify potential complications. Early detection of the risk of complications during pregnancy is also influenced by the mother's knowledge. Mothers' ignorance of signs of pregnancy risk can be influenced by various factors. Apart from the level of knowledge, exposure to information about the danger signs of pregnancy can also influence the mother's knowledge regarding recognizing the danger signs of pregnancy. The aim of this activity is to increase respondents' knowledge about the danger signs of pregnancy. Socialization methods in the form of lectures and questions and answers were used in this activity using leaflets and banner stands. Activity Results: Respondents were very enthusiastic about the material presented and there were several respondents who asked questions. The conclusion of this activity is that the better a pregnant woman understands these warning signs, the more she will be aware of the risks and complications that may occur related to her pregnancy.